Efektivitas Aplikasi Sistem Keuangan Desa (SISKEUDES) dalam Pengelolaan Keuangan Desa: (Studi Kasus di Desa Raporendu Kecamatan Nangapanda Kabupaten Ende) - Fatiah Zuliati; Laurensius P. Sayrani; Made N. D. Andaya; Mariayani O. Rene (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to describe and analyze the effectiveness of the Village Financial System Application (Siskeudes) in village financial management at all stages of financial management in Raporendu Village, Nangapanda District, Ende Regency. The focus of this research includes four main stages in village financial management, namely planning, budgeting, administration, and reporting and accountability, which are reviewed from three main indicators, namely transparency, accountability, and efficiency. The method used was a qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that Siskeudes has been quite effective in improving accountability and efficiency in every stage of village financial management. This application is able to speed up the administrative process, reduce costs, and support legal and administrative accountability. However, from the aspect of transparency, there are still obstacles in providing access to information periodically and at any time to the community, therefore, additional efforts are needed to strengthen public transparency such as the use of social media or village information boards. Technical constraints such as internet network constraints and the lack of public information media are also challenges in the implementation of the Village Financial System (Siskeudes). Thus, it can be concluded that the implementation of the Village Financial System Application (Siskeudes) has had a positive impact on public transparency